(3JMaI GdCUMGH hfRgI Chdi GdCdHGHs - (3Ch (B: (3CHi GdYHGS , CMeO Hf EHQGgje Hf YHO GdZfj GdSQhLis; (3eMeO GdTQLj GdRHjOj GdTGaYj , CHh YHO Gddg,J (B710 (3g` s
(3ChdgG (B:s
(3GeG HYO (B: (3agPG cJGH LeYJg ef cJH cKjQI GdZQGFH hGdYLGFH hSejJg hLYdJg ai NeSI CbSGe GdChd (B: (3ai GdYde hGdYbd hGdCOH GdKGfi (B: (3ai GdZRd hPcQ CjGe GdTHGH hGdeTjH s
(3BNQgG (B:s
(3hZSd GdQGS HGdHOQI bHd eNGdWI GdfSGA , hCcd GdSaQLd Ydi GdQjb , hGddg SHMGfg hJYGdi CYde HGdUhGH , hEdjg GdeQLY hGdeBH s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B140s
(3U (B362 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B141 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs